Correlation of IgA-EA Epstein Barr Virus with Risk Factors on Nasopharyngeal Carcinoma Type III - Roni Januardi; Yussy Afriani Dewi; Tonny Basriyadi (TALENTA PUBLISHER, 2020)
Introduction: Nasopharyngeal carcinoma (NPC) is a tumor derived from epithelial cells on the surface of the nasopharynx. The etiology of NPC is multifactorial, including genetic, environmental, and virological factors. Approximately 90% of NPC patients have a positive serology of EBV against IgA EA. Increased IgA EA titre was associated with NPC incidence. Objective: To examine the relationship of the increased value of IgA EA EBV titre on NPC type III with risk factor of mosquito coil smoke, smoking, salted fish and preserved food. Methods: This study was prospective observational analytic in the clinic of Oncology Head and Neck Surgery, Hasan Sadikin Hospital Bandung period July-October 2017, followed by 90 subjects who underwent history, histopathologic, and serology examination IgA EA by ELISA method. Statistical analysis using Mann Whitney test and Exact Fisher correlation test. Results: Based on serology IgA-EA with ELISA in NPC type III patient, the level of IgA-EA titres on subjects of salted fish and preserved foods 1.52 to 5.24, smoking 1.22 to 2.53, and mosquito coil smoke was found in the level of IgA EA 1.13 to 2.12. Statistical analysis of quantitative IgA EA in NPC type III with the risk factor of salted fish and preserved foods had the highest mean value (2.10 ± 0.692). Conclusion: There is correlation of the increase of IgA-EA EBV titration on NPC type III with risk factors of salted fish and preserved foods, smoking, and the use of mosquito coils smoke. There is no correlation risk factors of NPC type III with clinical stage.